Factors Associated With Progression of Lung Function Abnormalities in HIV-Infected Individuals. (1st December 2018) - Li, Yijia; Nouraie, Seyed Mehdi; Kessinger, Cathy; Weinman, Renee; Huang, Laurence; Greenblatt, Ruth M.; Kleerup, Eric; Kingsley, Lawrence; McMahon, Deborah; Fitzpatrick, Meghan; Morris, Alison
Abstract : Background: HIV is an independent risk factor for chronic obstructive pulmonary disease; however, baseline risk factors for lung function decline remain largely unknown in this population. Methods: HIV-infected participants in the Pittsburgh Lung HIV Cohort with at least 3 pulmonary function measurements between 2007 and 2016 were included. Pulmonary function testing including postbronchodilator (BD) spirometry and diffusion capacity for carbon monoxide (DLco) was performed every 18 months. We used a mixed-effect linear model to evaluate factors associated with pulmonary function testing and DLco decline and logistic regression models to evaluate factors associated with rapid FEV1 decline (defined as >80 mL per year) and any DLco decline. Results: Two hundred eighty-five HIV-infected participants were included. Median baseline CD4 cell count was 521 cells per micro liter, 61.9% had an undetectable HIV viral load at baseline, and 78.5% were receiving ART. Approximately 20% of participants met Global Initiative for Chronic Obstructive Lung Disease (GOLD) criteria for a diagnosis of chronic obstructive pulmonary disease at baseline. Older age and baseline GOLD stage 1 compared with stage 0 were associated with faster decline in post-BD FEV1%, whereas female sex was associated with slower decline. Similarly, female sex was associated with slower decline in DLco%. HIV-related factors including CD4 cell count, viral load, and ART use were not significantly associated with pulmonary function decline. Conclusions: Older age, male sex, and higher baseline GOLD stage were associated with more rapid post-BD FEV1% decline in HIV-infected individuals. Abstract : Supplemental Digital Content is Available in the Text.